A CHRONOLOGY OF ELECTRONIC WORD-OF-MOUTH RESEARCH IN TOURISM - Shen Ke; Wan Farha Wan Zulkiffli; Lu Man Hong (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The development of eWOM has influenced the tourism industry by providing opportunities for tourists to communicate with each other. And as there has been an increasing number of studies on eWOM in the tourism industry in recent years, there is a need to summarize these studies. The purpose of this study is to analyze the situation of eWOM research in the tourism industry since 2008, so as to summarize the development of eWOM research in the tourism industry and expand the scope of eWOM research. This study uses the published literature as the basis for research on eWOM in tourism according to the time sequence. By combing through the literature of previous studies, it is found that with the development of time, there are more and more research results on eWOM in the tourism industry, and the directions of research are becoming more and more diversified, and the research in recent years involves new science and technology, such as VR and AI technology. This study provides a necessary reference role for scholars and tourism practitioners.